2007
DOI: 10.1007/s00497-007-0049-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ethylene perception on sex expression in melon (Cucumis melo L.) as assessed by expression of the mutant ethylene receptor, At-etr1-1, under the control of constitutive and floral targeted promoters

Abstract: Sexual diversity expressed by Curcurbitaceae species is a primary example of developmental plasticity in plants. Ethylene, which promotes femaleness (carpel development), plays a key role in sex determination. We sought to determine the critical location for ethylene perception in developing floral primodia. The dominant negative Arabidopsis ethylene response mutant gene, etr1-1, was introduced into melon (Cucumis melo L.) plants under control of the constitutive cauliflower mosaic virus (CaMV) 35S promoter, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 52 publications
3
21
0
1
Order By: Relevance
“…Our Wndings were consistent with the reports that increased endogenous ethylene production enhanced femaleness in transgenic melon (Cucumis melo L.), indicated by studies with 35S promoter driven ACS genes (Papadopoulou et al 2005) and a CRC promoter driven dominant negative etr1 gene (Little et al 2007). Papadopoulou et al (2005) and Little et al (2007) indicated ethylene eVects on carpel development in transgenic melon.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our Wndings were consistent with the reports that increased endogenous ethylene production enhanced femaleness in transgenic melon (Cucumis melo L.), indicated by studies with 35S promoter driven ACS genes (Papadopoulou et al 2005) and a CRC promoter driven dominant negative etr1 gene (Little et al 2007). Papadopoulou et al (2005) and Little et al (2007) indicated ethylene eVects on carpel development in transgenic melon.…”
Section: Discussionsupporting
confidence: 92%
“…Papadopoulou et al (2005) and Little et al (2007) indicated ethylene eVects on carpel development in transgenic melon. However, we found no eVects of increased ethylene production on carpel development in transgenic P AP3 : CsACO2 Arabidopsis.…”
Section: Discussionmentioning
confidence: 98%
“…Several investigations have shown that phytohormones are involved in changes of flower type, number and ratio of flowers of different sex types, modifications of flowering time and of other traits related to sex expression (Noguera et al 2005, Papadopoulou et al 2005, Stankovic et al 2005, Yamasaki et al 2005, Little et al 2007, Boualem et al 2008, Ouzounidou et al 2008, Martin et al 2009). Most of these studies were performed in cucumber, the model plant for studying sex expression in Cucurbitaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Sex determination is another repercussion of altered ethylene perception in melon as reported by Little et al (2007). 145 The transgenic melon with At-etr1-1 gene resulting in reduced ethylene sensitivity showed change in sex expression.…”
mentioning
confidence: 99%
“…145 The transgenic melon with At-etr1-1 gene resulting in reduced ethylene sensitivity showed change in sex expression. The expression of etr1-1 was studied under the influence of a constitutive promoter, CaMV35S and tissue specific inflorescence targeted Apetela3 (AP3) and Crab's Claw (CRC) promoters.…”
mentioning
confidence: 99%